Extreme isomeric complexity of dissolved organic matter found across aquatic environments. Issue 2 (15th February 2018) - Hawkes, Jeffrey A.; Patriarca, Claudia; Sjöberg, Per J. R.; Tranvik, Lars J.; Bergquist, Jonas
Abstract: The natural aquatic environment contains an enormous pool of dissolved reduced carbon, present as ultra‐complex mixtures that are constituted by an unknown number of compounds at vanishingly small concentrations. We attempted to separate individual structural isomers from several samples using online reversed‐phase chromatography with selected ion monitoring/tandem mass spectrometry, but found that isomeric complexity still presented a boundary to investigation even after chromatographic simplification of the samples. However, it was possible to determine that the structural complexity differed among samples. Our results also suggest that extreme structural complexity was a ubiquitous feature of dissolved organic matter (DOM) in all aquatic systems, meaning that this diversity may play similar roles for recalcitrance and degradation of DOM in all tested environments.